Avaliação de impacto de ações de capacitação na área administrativa em uma Instituição Federal de Ensino Superior - Gonçalves, Pedro Rodrigues (2016)
The Human Resources Department is responsible for monitoring industry and professional development of employees, and the development through training and skills, one of the supports for the improvement of personnel management in the public service. This study was based on federal legislation, decrees 5,707/06 and 5,825/06, establishing criteria for continuos development of federal public servants, as well as training and Development Program adopted by the Federal University of Rio Grande do Norte-UFRN. The general objective of this study was to identify the direct and specific effects of the training actions, aimed at administrative area, about the behavior of the server in your office, in the Federal University of Rio Grande do Norte, and finally draw up and propose the implementation of a tool for in-depth impact assessment in the workplace. This was a study of a descriptive nature, exploratory, and qualitative and quantitative approach. The data collection took place by means of a questionnaire with closed questions. The sample consisted of 108 employees of central campus, 88 administrative technicians and 20 managers of administrative units. The results demonstrated the positive impact of the training program of the institution and the contribution permanent of the servers. Showed the high levels of satisfaction in the responses related to the applicability of the knowledge gained after training, as well as the direct and specific effects of the training actions in the administrative area clearly interfering positively in the server behavior in Office. Statistical analysis showed a Cronbach's Alpha's up 0.70, demonstrating thus data consistency classified as satisfactory in the search tool. The study contributed to the proposition of a model of in-depth impact assessment adapted to the reality of the institution.